TEORI PERMINTAAN (Komparasi Dalam Perspektif Ekonomi Konvensional Dengan Ekonomi Islam) - Elvira, Rini (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
The demand analysis is one of the most important analysis in microeconomics. Conventional economic outlook and Islamic economics about the real demand is almost the same. The fundamental difference lies in the source of sharia law and restrictions that are not found in conventional demand theory. The problems are interesting to study are (1) how the theory of demand in the conventional economic perspective? (2) how the theory of demand in Islamic economic perspective? (3) What are the things that makes the conventional demand theory to the theory of Islamic demand to be a bit different? Demand theory to explain the nature of the relationship between the level of commodity prices with the requested number of commodities in which this relationship can be explained by the law of demand says that the lower the price of a commodity the more commodities amount requested, and vice versa.Â Analisis permintaan merupakan salah satu analisis yang paling penting dalam mikroekonomi. Pandangan ekonomi konvensional dan ekonomi Islam tentang permintaan sesungguhnya hampir sama. Perbedaan mendasar terletak pada sumber hukum dan batasan syariâah yang tidak ditemui dalam teori permintaan konvensional. Permasalahan yang menarik untuk dikaji adalah (1) bagaimana teori permintaan dalam perspektif ekonomi konvensional? (2) bagaimana teori permintaan dalam perspektif ekonomi Islam? (3) Hal-hal apa yang membuat teori permintaan konvensional dengan teori permintaan Islami menjadi sedikit berbeda? Teori permintaan menjelaskan sifat hubungan antara tingkat harga komoditas dengan jumlah komoditas yang diminta dimana hubungan ini dapat dijelaskan melalui hukum permintaan yang mengatakan bahwa semakin rendah harga suatu komoditas maka akan semakin banyak jumlah komoditas yang diminta, begitupun sebaliknya.